Extracellular matrix and Hippo signaling as therapeutic targets of antifibrotic compounds for uterine fibroids - Md Soriful Islam; Sadia Afrin; Bhuchitra Singh; Friederike L. Jayes; Joshua T. Brennan; Mostafa A. Borahay; Phyllis C. Leppert; James H. Segars (Clinical and Translational Medicine, 2021)
Abstract Background Uterine fibroids are highly prevalent, collagen‐rich, mechanically stiff, fibrotic tumors for which new therapeutic options are needed. Increased extracellular matrix (ECM) stiffness activates mechanical signaling and Hippo/YAP promoting fibroid growth, but no prior studies have tested either as a therapeutic target. We tested the hypothesis that injection of a purified form of collagenase Clostridium histolyticum (CCH) that selectively digests type I and type III collagens would alter ECM stiffness, Hippo signaling, and selectively reduce fibroid cell growth. We also used two FDA‐approved drugs, verteporfin and nintedanib, to elucidate the role of Hippo/YAP signaling in uterine fibroid and myometrial cells. Methods The clinical trial was registered (NCT02889848). Stiffness of samples was measured by rheometry. Protein expression in surgical samples was analyzed via immunofluorescence. Protein and gene expression in uterine fibroid or myometrial cell lines were measured by real time PCR and western blot, and immunofluorescence. Results Injection of CCH at high doses (0.1–0.2 mg/cm3) into fibroids resulted in a 46% reduction in stiffness in injected fibroids compared to controls after 60 days. Levels of the cell proliferation marker proliferative cell nuclear antigen (PCNA) were decreased in fibroids 60 days after injection at high doses of CCH. Key Hippo signaling factors, specifically the transcriptionally inactive phosphorylated YAP (p‐YAP), was increased at high CCH doses, supporting the role of YAP in fibroid growth. Furthermore, inhibition of YAP via verteporfin (YAP inhibitor) decreased cell proliferation, gene and protein expression of key factors promoting fibrosis and mechanotransduction in fibroid cells. Additionally, the anti‐fibrotic drug, nintedanib, inhibited YAP and showed anti‐fibrotic effects. Conclusions This is the first report that in vivo injection of collagenase into uterine fibroids led to a reduction in Hippo/YAP signaling and crucial genes and pathways involved in fibroid growth. These results indicate that targeting ECM stiffness and Hippo signaling might be an effective strategy for uterine fibroids.